Paddy Drying in Batch Fluidized Bed and Scale-up Simulation in Continuous Operation Mode - Suherman, Suherman; Djaeni, Mohammad; Wardhani, Dyah Hesti; Kumoro, Andri Cahyo (KnE Life Sciences, 2017)
The objective of this research is to develop the industrial-scale fluid bed dryer for paddy by scale-up of lab-scale experimental data. The developed dryer was conducted by simulation using a two phase model. Firstly, the experimental works by using lab-scale batch fluid bed dryer, was conducted to determine the drying curve of paddy (Xin 0.32 kg/kg dry base). In the experimental works,the inlet air temperature was varied (°C): 40; 50; 60. The drying rate curves as a function of moisture content showed only decreasing drying rate period. Then, a very good agreement between the measured and simualtion results of the profile of moisture content in solids was produced by simulator. Finally, asimulated continuous fluidized bed dryer for paddy with dimension 5 m of length and 1.5 of width was succesfully performed, in which the influence of mass solid flow rate 0.1; 0.2; 0.4 tons/h, height of bed 0.25; 0.50; 0.75 m, and air temperature 50; 70; 100 °C on drying process were studied. Keywords: Paddy; fluid bed dryer; batch, contonious; modelling; simulation